2021
DOI: 10.7717/peerj.11490
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome of the Sunda pangolin (Manis javanica) reveals its adaptation to specialized myrmecophagy

Abstract: Background The gut microbiomes of mammals are closely related to the diets of their hosts. The Sunda pangolin (Manis javanica) is a specialized myrmecophage, but its gut microbiome has rarely been studied. Methods Using high-throughput Illumina barcoded 16S rRNA amplicons of nine fecal samples from nine captive Sunda pangolins, we investigated their gut microbiomes. Results The detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
0
17
1
Order By: Relevance
“…The dominant genera in group 1 were Staphylococcus, Porphyromonas , and Anaerococcus ; the dominant genera in group 2 were Staphylococcus, Anaerococcus , and Bacteroides ; and the dominant genera in group 3 were Staphylococcus, Bacteroides , and Streptococcus . This was different from previous studies that reported Lactobacillus, Escherichia / Shigella , and Clostridium sensu stricto 1 as the dominant genera (Ma et al, 2018 ; Liu et al, 2021 ; Yan et al, 2021 ; Zhang et al, 2021 ). From now on, this is the first study to identify the dominant intestinal microbial species in pangolins using 16S full-length sequencing.…”
Section: Discussioncontrasting
confidence: 76%
“…The dominant genera in group 1 were Staphylococcus, Porphyromonas , and Anaerococcus ; the dominant genera in group 2 were Staphylococcus, Anaerococcus , and Bacteroides ; and the dominant genera in group 3 were Staphylococcus, Bacteroides , and Streptococcus . This was different from previous studies that reported Lactobacillus, Escherichia / Shigella , and Clostridium sensu stricto 1 as the dominant genera (Ma et al, 2018 ; Liu et al, 2021 ; Yan et al, 2021 ; Zhang et al, 2021 ). From now on, this is the first study to identify the dominant intestinal microbial species in pangolins using 16S full-length sequencing.…”
Section: Discussioncontrasting
confidence: 76%
“…In contrast, the Rank abundance curve reflects the richness and evenness of species in samples. These curves have been reported in other mammals, including humans (29), wildlife species (30), and Sunda pangolin (Manis javanica) (31). ANOSIM analysis is a nonparametric test that determines whether group variation is significantly larger than group variation, which aids in determining the reasonability of group division.…”
Section: Discussionmentioning
confidence: 62%
“…More-detailed studies are required to determine whether the core genera are potentially interacting with a hyena’s metabolism. We do know that Bacteroides forms part of the core microbiome or is highly abundant in the guts of wild cats ( Felis silvestris catus ), coyotes ( Canis latrans ), raccoon dogs ( Nyctereutes procyonoides ), black-backed jackals ( Canis mesomelas ), and myrmecophagous pangolins ( Manis javanica ) ( 84 87 ). Members of this bacterial genus are known to be functionally involved in the degradation of protein and are related to a high-fat and protein-based diet ( 88 ).…”
Section: Discussionmentioning
confidence: 99%